Pengaruh Penggunaan Strategi Pembelajaran Reciprocal Teaching terhadap Peningkatan Hasil Belajar Mata Pelajaran Informatika pada Kelas VII di MTsN 9 Agam - Intan Rahmayanti; Supriadi Supriadi; Supratman Zakir; Liza Efriyanti (ALSYS, 2026)
Relatively low student learning outcomes and limited courage and motivation to express ideas formed the background for implementing the reciprocal teaching instructional strategy in the Informatics subject. This study aimed to measure the impact of reciprocal teaching on the Informatics learning outcomes of seventh-grade students at MTsN 9 Agam. The research employed an experimental method with a quasi-experimental design, specifically a nonequivalent control group design. The population comprised all seventh-grade students of MTsN 9 Agam in the 2024–2025 academic year, with a sample of 50 students selected using a non-probability purposive sampling technique. Data were collected using an objective-format post-test and analyzed through prerequisite tests (normality and homogeneity tests) followed by a parametric statistical test in the form of a t-test. The analysis showed that the calculated t-value (tₕᵢₜᵤₙg = 3.116) was greater than the critical t-value (tₜₐᵦₑₗ = 2.011), with a significance value (two-tailed p-value) of 0.003 < 0.05, so H₀ was rejected and Hₐ was accepted. These findings indicate a significant effect of the reciprocal teaching instructional strategy on the Informatics learning outcomes of seventh-grade students at MTsN 9 Agam. Accordingly, reciprocal teaching can be recommended as an effective alternative instructional strategy to improve student learning outcomes and contribute to the development of innovative learning models in schools.